Viral Enhancement of Nasal Colonization with Haemophilus influenzae Type b in the Infant Rat - Michaels, Richard H (Pediatr Res, 1983)
Summary: Infant rats infected with influenza A virus, Sendai (parainfluenza 1) virus or rat coronavirus were used to determine whether viral infection increases the intensity of nasal colonization with Haemophilus influenzae type b (HIB). Intranasal inoculation of HIB in rats previously infected with each of these viruses resulted in nasal HIB titers at least 100-fold higher than those for controls during the first 2 wk after HIB inoculation, and as much as 10,000-fold higher during the first week. Children with cough, sneezing, or rhinorrhea could be effective disseminators of HIB if they were as heavily and persistently colonized as these virus-infected animals.